The interdisciplinary practice of teachers of science in environmental Education Middle school students (Research, Society and Development, 2022)
The article focused on knowing the interdisciplinary practice of teachers in relation to high school students regarding environmental education. Interdisciplinary practice in the school environment has been considered essential in the teaching and learning process, as it enables it to occur in an innovative, integrative, participatory and dynamic way, among others. The general objective of the research was to demonstrate how the interdisciplinary pedagogical practices of High School Science teachers are carried out in relation to environmental education. Considering that Environmental Education is related to the preservation of the environment and sustainable development, the interdisciplinary practice of Science teachers can contribute to this process, insofar as it enables students to effectively participate in the defense of the environment. Therefore, the study was developed from literary, descriptive research, through a qualitative approach, where it was possible to observe the curricular activities developed by high school Science teachers, in addition to data collection through INEP, describing the routine of teachers and manager where it was possible to identify the pedagogical practices aimed at the preservation of the environment. Thus, it is concluded that the pedagogical and interdisciplinary practice of the teachers directly influences the students' perception, bringing changes in the development of educational practices and training of students as protectors of the environment.